Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
Keywords: _r:AddedByZotZen